Redescription of the rheophilous cladocera Camptocercus vietnamensis Than, 1980 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2011)
Little-known Vietnamese chydorid cladocera, Camptocercus vetnamensis Than, 1980 is redescribed on the material from Cat Tien national park, South Vietnam. Detailed morphology of limbs is described for the first time. In some features, C. vietnamensis is similar to C. uncinatus Smirnov, 1971, but can be easily differentiated from it by smaller size, morphology of postabdomen and labrum. C. vietnamensis is the only species of the genus Camptocercus strictly confined to the rheic conditions.